Impeachment an American history - Engel, Jeffrey A. 1972-; Meacham, Jon 1969-; Baker, Peter 1967-; Naftali, Timothy J. 1962- (Modern Library, 2018)
"Four experts on the American presidency review the only three impeachment cases from history--against Andrew Johnson, Richard Nixon, and Bill Clinton--and explore its power and meaning for today. Impeachment is rare, and for good reason. Designed to check tyrants or defend the nation from a commander-in-chief who refuses to do so, the process of impeachment outlined in the Constitution is what Thomas Jefferson called "the most formidable weapon for the purpose of a dominant faction that was ever contrived." It nullifies the will of voters, the basic foundation of legitimacy for all representative democracies. Only three times has a president's conduct led to such political disarray as to warrant his potential removal from office, transforming a political crisis into a constitutional one... These three cases highlight factors beyond the president's behavior that impact the likelihood and outcome of an impeachment: the president's relationship with Congress, the power and resilience of the office itself, and the polarization of the moment. This is a realist, rather than hypothetical, view of impeachment that looks to history for clues about its future--with one obvious candidate in mind"--
Keywords: USA -- Präsident; Geschichte; Impeachments -- United States -- History; History -- United States -- General; Political science -- Government -- Executive Branch; History -- Essays; Impeachment; Absetzung; USA